2018
DOI: 10.1080/0284186x.2018.1478126
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary and gastrointestinal toxicity among patients with localized prostate cancer treated with conventional versus moderately hypofractionated radiation therapy: systematic review and meta-analysis

Abstract: In meta-analysis of the available randomized trials on moderate HRT versus CRT for prostate cancer, acute and late GU toxicity were similar for both treatment schemes. While HRT was associated with higher acute GI toxicity, late toxicity was similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…For HDR+EBRT, Ishiyama et al reported 5-and 10-year accumulated rates of late Grade ≥2 GU toxicities were 16.7% and 26.7% in 3424 Asian patients [10]. Our data (Conv EBRT 9.2% and 13.8%, HDEBRT 5.6% and not available, HDR +EBRT 10.5%, and 23% at 5-and 10-years) concurred to Japanese and Asian data and it seems lower than the previous review [31].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For HDR+EBRT, Ishiyama et al reported 5-and 10-year accumulated rates of late Grade ≥2 GU toxicities were 16.7% and 26.7% in 3424 Asian patients [10]. Our data (Conv EBRT 9.2% and 13.8%, HDEBRT 5.6% and not available, HDR +EBRT 10.5%, and 23% at 5-and 10-years) concurred to Japanese and Asian data and it seems lower than the previous review [31].…”
Section: Discussionsupporting
confidence: 82%
“…For GU toxicity, Carvalho, et al made a systematic review and meta-analysis and reported around 28% of late GU toxicity at 12 months or more after EBRT [31]. Takemoto reported 7.9-12.4% of GU Grade ≥2 ratio at 6-10 years using IMRT in Japan [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, RT-related genitourinary and gastrointestinal toxicities are frequently observed, and these can manifest as urinary frequency, dysuria, urgency, rectal pain, stool frequency, or rectal bleeding [15][16][17]. A recent systemic review and meta-analysis by Carvalho et al reported that the incidence of acute genitourinary and gastrointestinal toxicity was 31.9% and 21.9% in patients who underwent conventional RT [18]. Moreover, the late genitourinary and gastrointestinal toxicities were 28.0% and 16.2%, respectively.…”
Section: Plos Onementioning
confidence: 99%
“…Nevertheless, there always has been a concern about possible late adverse effects linked to HFRT. Several studies have shown statistically similar late toxicity rates between the two fractionation schedules [39,40]. However, Alluwini et al, who used the highest EQD2 (90.4 Gy), reported an increased cumulative incidence of late GI toxicity (stool frequency) grade ≥ 2 (1.19 Hazard Ratio (HR) [95% CI 0.93-1.52]) and an increased cumulative incidence of late GU toxicity (frequency, nocturia and incontinence) grade ≥ 3 with HFRT versus CFRT (19.0% [95% CI 15.2-23.2] vs. 12.9% [9.7-16.7], respectively; p = 0.021) [22].…”
Section: Discussionmentioning
confidence: 98%